LEPTOSPIROSIS PADA MANUSIA DI KABUPATEN BANYUMAS, PROVINSI JAWA TENGAH - Bina Ikawati; Sunaryo Sunaryo; Dyah Widiastuti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2013)
ABSTRACT. Leptospirosis is one of infected diseases that caused by bacteria pathogen called Leptospira Sp,transmitted direct or indirect from infected animal to human, also known as zoonotic deseases. Indonesia includein middle category for leptospirosis incidence with 1-10 per 100.000 population.Leptospirosis in Central Java at2011 reported in Demak, Purworejo, Klaten, Pati, Wonogiri, Cilacap, Jepara District, Semarang District andSemarang City. Clinical leptospirosis in Banyumas District found but underreported. Aimed of this research wasto confirm leptospirosis at human in Banyumas district. Cross sectional design by case screening in 3 hospital and2 Primary Health Care at Juni-November 2012. Sera from patient examine by leptotec IgG IgM and MAT(Microscopic Aglutination Test), risk factor tracer had been done in patient from Banyumas. As much 25 clinicalleptospirosis examinated with laboratory test showed 6 serra positive by leptotec IgG IgM and with MAT(Microscopic Aglutination Test). MAT test showed 4 sera clinical leptospirosis that reactive with Leptospira Spand 1 negative but reactive at low titre 1:80. Risk factor of leptospirosis was flood and poor housing, bad hygienesanitation, bad waste management. Leptospirosis case confirmed in Banyumas